Clinical Marine Toxicology: A European Perspective for Clinical Toxicologists and Poison Centers - Luc De Haro; Corinne Schmitt (Toxins, 2013)
Clinical marine toxicology is a rapidly changing area. Many of the new discoveries reported every year in Europe involve ecological disturbances—including global warming—that have induced modifications in the chorology, behavior, and toxicity of many species of venomous or poisonous aquatic life including algae, ascidians, fish and shellfish. These changes have raised a number of public issues associated, e.g., poisoning after ingestion of contaminated seafood, envenomation by fish stings, and exposure to harmful microorganism blooms. The purpose of this review of medical and scientific literature in marine toxicology is to highlight the growing challenges induced by ecological disturbances that confront clinical toxicologists during the everyday job in the European Poison Centers.